Flavonol rhamnosylation indirectly modifies the cell wall defects of RHAMNOSE BIOSYNTHESIS1 mutants by altering rhamnose flux. (6th April 2018) - Saffer, Adam M.; Irish, Vivian F.
Summary: Rhamnose is required in Arabidopsis thaliana for synthesizing pectic polysaccharides and glycosylating flavonols. RHAMNOSE BIOSYNTHESIS1 ( RHM1 ) encodes a UDP‐l ‐rhamnose synthase, and rhm1 mutants exhibit many developmental defects, including short root hairs, hyponastic cotyledons, and left‐handed helically twisted petals and roots. It has been proposed that the hyponastic cotyledons observed in rhm1 mutants are a consequence of abnormal flavonol glycosylation, while the root hair defect is flavonol‐independent. We have recently shown that the helical twisting of rhm1 petals results from decreased levels of rhamnose‐containing cell wall polymers. In this study, we found that flavonols indirectly modify the rhm1 helical petal phenotype by altering rhamnose flux to the cell wall. Given this finding, we further investigated the relationship between flavonols and the cell wall in rhm1 cotyledons. We show that decreased flavonol rhamnosylation is not responsible for the cotyledon phenotype of rhm1 mutants. Instead, blocking flavonol synthesis or rhamnosylation can suppress rhm1 defects by diverting UDP‐l ‐rhamnose to the synthesis of cell wall polysaccharides. Therefore, rhamnose is required in the cell wall for normal expansion of cotyledon epidermal cells. Our findings suggest a broad role for rhamnose‐containing cell wall polysaccharides in the morphogenesis of epidermal cells. Significance Statement: Rhamnose is a component of both pectic polysaccharides and flavonols; we show that blocking flavonol synthesis or flavonol rhamnosylation can suppress the cell wall defects caused by mutations in RHAMNOSE BIOSYNTHESIS1 . Our findings suggest a broad role for rhamnose‐containing cell wall polysaccharides in the morphogenesis of epidermal cells.